Cetuximab, docetaxel, and cisplatin versus platinum, fluorouracil, and cetuximab as first-line treatment in patients with recurrent or metastatic head and neck squamous-cell carcinoma (GORTEC 2014-01 TPExtreme): a multicentre, open-label, randomised, phase 2 trial. Issue 4 (April 2021) - Guigay, Joël; Aupérin, Anne; Fayette, Jérôme; Saada-Bouzid, Esma; Lafond, Cédrik; Taberna, Miren; Geoffrois, Lionnel; Martin, Laurent; Capitain, Olivier; Cupissol, Didier; Castanie, Hélène; Vansteene, Damien; et al.
Summary: Background: Results from a phase 2 trial of the TPEx chemotherapy regimen (docetaxel–platinum–cetuximab) showed promising results, with a median overall survival of 14·0 months in first-line recurrent or metastatic head and neck squamous-cell carcinoma (HNSCC). We therefore aimed to compare the efficacy and safety of the TPEx regimen with the standard of care EXTREME regimen (platinum–fluorouracil–cetuximab) in this setting. Methods: This was a multicentre, open-label, randomised, phase 2 trial, done in 68 centres (cancer centres, university and general hospitals, and private clinics) in France, Spain, and Germany. Eligible patients were aged 18–70 years with histologically confirmed recurrent or metastatic HNSCC unsuitable for curative treatment; had at least one measurable lesion according to Response Evaluation Criteria in Solid Tumors version 1.1; and had an Eastern Cooperative Oncology Group (ECOG) performance status of 1 or less. Participants were randomly assigned (1:1) using the TenAlea website by investigators or delegated clinical research associates to the TPEx regimen or the EXTREME regimen, with minimisation by ECOG performance status, type of disease evolution, previous cetuximab treatment, and country. The TPEx regimen consisted of docetaxel 75 mg/m 2 and cisplatin 75 mg/m 2, both intravenously on day 1, and cetuximab on days 1, 8, and 15 (intravenously 400 mg/m 2 on day 1 of cycle 1 and 250 mg/m 2 weekly subsequently). Four cycles were repeated every 21 days with systematic granulocyte colony-stimulating factor (G-CSF) support at each cycle. In case of disease control after four cycles, intravenous cetuximab 500 mg/m 2 was continued every 2 weeks as maintenance therapy until progression or unacceptable toxicity. The EXTREME regimen consisted of fluorouracil 4000 mg/m 2 on day 1–4, cisplatin 100 mg/m 2 on day 1, and cetuximab on days 1, 8, and 15 (400 mg/m 2 on day 1 of cycle 1 and 250 mg/m 2 weekly subsequently) all delivered intravenously. Six cycles were delivered every 21 days followed by weekly 250 mg/m 2 cetuximab as maintenance therapy in case of disease control. G-CSF support was not mandatory per the protocol in the EXTREME regimen. The primary endpoint was overall survival in the intention-to-treat population; safety was analysed in all patients who received at least one dose of chemotherapy or cetuximab. Enrolment is closed and this is the final analysis. This study is registered at ClinicalTrials.gov, NCT02268695 . Findings: Between Oct 10, 2014, and Nov 29, 2017, 541 patients were enrolled and randomly assigned to the two treatment regimens (271 to TPEx, 270 to EXTREME). Two patients in the TPEx group had major deviations in consent forms and were not included in the final analysis. Median follow-up was 34·4 months (IQR 26·6–44·8) in the TPEx group and 30·2 months (25·5–45·3) in the EXTREME group. At data cutoff, 209 patients had died in the TPEx group and 218 had died in the EXTREME group. Overall survival did not differ significantly between the groups (median 14·5 months [95% CI 12·5–15·7] in the TPEx group and 13·4 months [12·2–15·4] in the EXTREME group; hazard ratio 0·89 [95% CI 0·74–1·08]; p=0·23). 214 (81%) of 263 patients in the TPEx group versus 246 (93%) of 265 patients in the EXTREME group had grade 3 or worse adverse events during chemotherapy (p<0·0001). In the TPEx group, 118 (45%) of 263 patients had at least one serious adverse event versus 143 (54%) of 265 patients in the EXTREME group. 16 patients in the TPEx group and 21 in the EXTREME group died in association with adverse events, including seven patients in each group who had fatal infections (including febrile neutropenia). Eight deaths in the TPEx group and 11 deaths in the EXTREME group were assessed as treatment related, most frequently sepsis or septic shock (four in each treatment group). Interpretation: Although the trial did not meet its primary endpoint, with no significant improvement in overall survival with TPEx versus EXTREME, the TPEx regimen had a favourable safety profile. The TPEx regimen could provide an alternative to standard of care with the EXTREME regimen in the first-line treatment of patients with recurrent or metastatic HNSCC, especially for those who might not be good candidates for up-front pembrolizumab treatment. Funding: Merck Santé and Chugai Pharma.